El aporte del derecho internacional de los derechos humanos a la constitucionalización del derecho post 1945 - Burneo Labrín, José (2013)
This article base line bears on the relevance of the process– developed after 1945– of law’s constitutionalization, its foundations established and main characteristics. This process is framed by HumanRights fully implementation, such as rejection of impunity concerning serious human rights violations, respect to due process, the integrality and indivisibility of human rights, also respect to indigenous people and limits to state of emergency. Finally, through reviewing laws for compliance, the author highlights the importance of jurisdictional bodies for an effective fulfillment of constitutional and supranational rules signed by the States.